A statistical analysis plan for the efficiency and safety of Chinese herbal medicine used concurrently with topical therapy for psoriasis vulgaris. Issue 1 (December 2016) - Lu, Liming; Xuan, Meiling; Yan, Yuhong; Li, Geng; Zhou, Li; Wen, Zehuai; Lu, Chuanjian
Abstract Background Psoriasis vulgaris (PV) has been causing increasing concern due to its highly prevalent, harmful and therapy-resistant characteristics. The YXBCM01 (Chinese herbal medicine) for PV trial evaluates the effects of YXBCM01 on relapse rate in patients suffering from PV. As an update to the published design and method for the trial, this paper presents the statistical plan for the main publication to avoid the risk of outcome reporting bias, selective reporting, and data-driven results. Methods/design This trial is a multicenter, randomized, double-blind, placebo-controlled, parallel-group clinical trial. A total of 600 PV patients (300 in each group) will be randomized to one of two arms: participants in the experimental group will receive the YXBCM01 granule 5.5 g twice daily for 12 weeks. Placebo granules are given to patients in the control group at a dose of 5.5 g twice daily for 12 weeks. The sequential topical therapy is administrated simultaneously to all eligible patients by using calcipotriol betamethasone ointment once daily (a treatment area of up to 30 % body surface area (BSA), fingertip unit is recommended) in the first 4 weeks (maximum of 100 g weekly), followed by calcipotriol betamethasone ointment once daily for the remaining 8 weeks (maximum of 100 g weekly). The primary outcome measure is relapse rate in the treatment period and follow-up period. The secondary outcome measures include time to relapse, time to onset, rebound rate, cumulative consumption of topical medicine, visual analog scale (VAS), BSA, the Dermatology Life Quality Index (DLQI) and the Medical Outcomes Study (MOS) 36-item short form health survey (SF-36). Conclusions Application of this statistical analysis plan to the YXBCM01 for PV trial will facilitate unbiased evaluation of these important clinical data. This study will provide evidence regarding the value of YXBCM01 as an intervention for PV patients. Trial registration Chinese Clinical Trial Registry:ChiCTR-TRC-13003233, registered on 26 May 2013.